Effect of Encapsulated Propolis on Microbial Quality and Antioxidant Activity of Yoghurt - Günhan, Rabia Serpil; Keskin, Şaban; Telli, Nihat; Takma, Çiğdem; Kolaylı, Sevgi (Progress in Nutrition, 2022)
Yoghurt, a functional food, has been gained much attention on its production and consumption in the world. It is a fermented dairy product that contains lots of nutrional components. Some manufacturers have used some additives to extend the shelf life of yoghurt. Propolis could be alternative food additive instead of synthetic ones. Propolis is a resinous mixture collected by honeybees for hive protection. In this study functional yoghurt fortified with microencapsulated propolis was prepared. Ethanol extract of propolis was encapsulated by using sodium alginate, pectin and gelatin separately. The effect of microencapsulated propolis on physicochemical characteristics and microbial quality of yoghurts was tested. Especially the effect of propolis on unwanted microorganisms during storage was studied. Our results clearly showed that fortified yoghurt samples were better in terms of microbial quality during storage. It could be concluded that propolis could be a natural preservative for extending the shelf life of yoghurt.